The Influence of the Problem-Based Learning Model Assisted by Pop-up Books on Students' Science Literacy - Risa Putri Aprianti; Nenden Permas Hikmatunisa; Nurdiansyah (Lembaga Bale Literasi, 2026)
This study was motivated by the low level of science literacy among elementary school students, particularly regarding the topic of light and its properties. Students are not sufficiently engaged in the learning process, resulting in incomplete mastery of the material. This study aims to determine the effect of a Problem-Based Learning model supplemented with a pop-up book and to assess improvements in science literacy between students who received this model and those who received the scientific inquiry approach. This study employed a quantitative approach using a quasi-experimental method and a non-equivalent control group design. The population consisted of 72 fifth-grade students at SDN Sarimulya 3. The sample comprised 24 students from Class V-A as the experimental group and 24 students from Class V-C as the control group. Data were collected through pre-test and post-test assessments and analyzed using the N-Gain test, simple linear regression, and the independent samples t-test. The results showed that the problem-based learning model aided by pop-up books had a significant effect on science literacy, with R = 0.753, R-squared = 0.567, and a significance value of 0.000 < 0.05. Furthermore, the science literacy of students in the experimental class was higher than that of the control class, with a post-test average of 83.33 and an N-Gain score of 0.59, while the control class had a post-test average of 76.88 and an N-Gain score of 0.42. Thus, the problem-based learning model aided by pop-up books is more effective in improving science literacy than the use of the scientific approach.